Asesmen Keterampilan Berpikir Tingkat Tinggi - Mahanal, Susriyati (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title: Higher Order Thinking Skills Assessment]. At present, the scope of transformation seems endless, from cars that park themselves without drivers to the production of cars on location through 3D printing. The wearable technology is controlled by the human mind. The coming era of individuals who can face the complexities of life are individuals who have competencies that cannot be replaced by robots, such as empathy, inspiring skills, and higher-order thinking skills. Severe challenges for education to prepare students to become workers who can adapt to new tasks and processes can be overcome by practising higher-order thinking skills. Higher-order thinking skills (HOTS) can be trained in schools through the application of constructivist-based learning models. In education, interrelated models, goals, and assessments are called triangle education anchors. Thus, if you want to learn objectives to achieve higher-order thinking skills, then the implementation of learning (models) and their measurement (assessment) must be managed to achieve these goals.